"Real‐life" outcome of gastrointestinal tumor therapies: A single‐center comparative study. Issue 5 (30th May 2019) - Buratti, Thomas; Mair, Maximilian; Mühlberger, Nikolai; Mitterer, Manfred
Abstract: Background: Despite of the ongoing improvements in gastrointestinal oncology, it remains unclear whether results of randomized controlled trials are achievable in daily clinical practice of nonacademic environments. Aim: This study aims at assessing a potential efficacy‐effectiveness gap in gastrointestinal cancer treatment. Methods and Results: Data from 656 gastrointestinal cancer patients treated between 2007 and 2015 in a medium‐sized, nonacademic day hospital oncology unit in Italy were analyzed. Probability of survival and median overall survival as efficacy indicators and the occurrence of grades 3 to 4 adverse events as safety indicators were compared with randomized phase II/III trials of respective entities. Outcomes were well comparable between published data and the real‐life setting. In resectable gastroesophageal cancer, 1‐year survival after treatment initiation was greater (relative risks [RR] = 1.3, p  = .007), while patients with adjuvant chemotherapy for pancreatic cancer exhibited inferior 2‐year survival (RR = 0.7, p  = .048) compared with referenced trials. At our unit, neutropenia was less frequent (5.8% vs 27.8%, p  = .039) in palliative chemotherapy for pancreatic cancer, as was peripheral neuropathy for stage II/III colon cancer (3.9% vs 12.5%, p  = .027). Conclusion: The "real‐life" findings of this study support the efficacy and safety data achieved in landmark trials of gastrointestinal oncology.